Pengaruh konten post dan testimoni di sosial media Instagram terhadap minat beli konsumen pada produk industri otomotif - Nur Aida Choirunnisa; Sri Walyoto (Journal of Economics and Business Research (JUEBIR), 2023)
Often consumers experience problems when searching for automotive products on social media, namely lack of product information and trust in a business account due to the company's lack of consistency in building communication with potential customers through post content. Of course this can affect consumer buying interest. This study aims to determine the effect of post content and testimonials on social media Instagram on consumer buying interest in automotive industry products at Rizki CB's workshop. This type of research is quantitative research with a survey method that is distributed via online/google form questionnaires to followers of the Instagram account @rizki.cb. The sampling technique used non-probability sampling method with a total sample of 100 people. While data processing is done using SPSS 24.00 for window software. The results of this study indicate that: (1) Post content has a positive and significant effect on consumer buying interest. (2) Testimonials have a positive and significant effect on consumer buying interest. (3) Post content and testimonial variables together have a significant effect on purchase intention. This can be a consideration for Rizki CB's business in increasing buying interest or attracting consumer attention to a product through social media to create post content on Instagram social media that contains complete information according to the needs of potential customers (account followers) and creates its own uniqueness.